A study on the level of satisfaction based on featured facilities for the convenience usage towards passengers case study: Low Cost Carrier Terminal (LCCT), Sepang / Azmil Rohimie Zakaria - Zakaria, Azmil Rohimie (2010)
This Academic Project has been written to study on the level of satisfaction based on its featured facilities among passengers who tend to use it. Facility Management (FM) is a balance between technical, managerial and business acumen that may be related to operational, tactical and strategic decision-making processes. The operational activities are concerned with effective functionality of service, the tactical with the organisation and administration procedures and the strategic with the match between facilities and corporate objectives. It is essentially a management function and it is at the strategic level that FM can have the greatest impact; to be involved with forward planning decisions. Successful FM teams will be able to embrace the language of the core organisations they serve, clarify and serve their strategic contribution in terms of business relevant outcomes (Hallam, 2000). The study examines the passengers perspective towards the facilities been provided. Sources of data are gathered by the author from literature review of previous researches, journals and others. Utilizing a set of questionnaire, the study focuses on the level of satisfaction by investigating particulars aspects related to facilities. Besides that, the study also identifies suggestions that can help improving the services of the facilities. The questionnaires used to collect the data distributed by hand and the sample size of this research is 50 passengers as respondents.